2020
DOI: 10.3389/fphar.2020.574533
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation for the Treatment of Inflammatory Bowel Disease: An Update

Abstract: Fecal microbiota transplantation (FMT) has successfully been applied for the treatment of recurrent Clostridioides difficile infection (CDI), which has led to studies on its application to other gastrointestinal diseases and extraintestinal diseases associated with gut microbiota dysbiosis. Recently, the results of FMT for patients with inflammatory bowel disease (IBD) have been encouraging. However, studies have not fully clarified the clinical application of this emerging therapy. Here, we aimed to review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 64 publications
0
69
0
2
Order By: Relevance
“…Indeed, this procedure can be difficult to set up and control. Donor choice is an especially important consideration 20 because donor incompatibility can lead to alterations in nutrient absorption, promote the onset of chronic disease, or transfer undesired microorganisms 21 . Recently, in murine models, treatments employing single bacterial strains have been successfully used to modulate gut microbial populations 22 and restore gastrointestinal health by reducing tissue damage and levels of pro-inflammatory cytokines 12 , 23 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this procedure can be difficult to set up and control. Donor choice is an especially important consideration 20 because donor incompatibility can lead to alterations in nutrient absorption, promote the onset of chronic disease, or transfer undesired microorganisms 21 . Recently, in murine models, treatments employing single bacterial strains have been successfully used to modulate gut microbial populations 22 and restore gastrointestinal health by reducing tissue damage and levels of pro-inflammatory cytokines 12 , 23 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple case studies and several randomized trials have explored this concept in patients with IBD. While most randomized studies involving patients with UC revealed that FMT had a significant impact on induction of remission (Stallmach et al, 2019;Tan et al, 2020), its efficacy has not been verified for patients with CD. Placebo-controlled trials involving patients with UC revealed that, although one out of every 3 to 4 patients achieved remission after FMT, one-time or short-term FMT leads to clinical failure over time.…”
Section: Fecal Microbiota Transplantation: Ready For Prime Time?mentioning
confidence: 99%
“…To address this problem, repeat colonoscopic FMT was performed once every 8 weeks in patients with UC; this led to the maintenance of both endoscopic and histologic remission. The role of FMT for the treatment of CD has been explored in case series and a single randomized study (Tan et al, 2020). Despite the very heterogeneous approaches, including different applications, target criteria, and patient groups (children, teenagers, or adults with CD), the data suggest an ∼30% probability (76/255 patients) of remission in response to FMT.…”
Section: Fecal Microbiota Transplantation: Ready For Prime Time?mentioning
confidence: 99%
“…Out of the 661 IBD patients who underwent FMT, clinical remission that was observed in patients with CD and pouchitis was around 50.5% and 21.5%. A higher number of FMT infusions showed improved remission in UC patients when administered throughout the lower GI tract [68][69][70][71] and a randomized control trial was conducted in 2015, wherein FMT was administered via a nasoduodenal tube [72] . In patients with severe, resistant UC, the effect of FMT was evaluated [73] where in 27% patients receiving FMT compared to 8% patients receiving placebo displayed no difference in adverse effects.…”
Section: Gut Microbiota/fecal Microbiota Transplantation (Fmt)mentioning
confidence: 99%
“…The 16S ribosomal RNA-sequence revealed that the intestinal flora in patients diagnosed with ulcerative colitis was different from that of donors. Improvement in the scores for diarrhoea, abdominal pain, and mucous membrane lesions changes due to abundance of bacterial flora and for patients with this disease, fecal microbiota transplantation would be of great therapeutic benefit [69]. In a study on UC patients has conducted wherein 73 adults with mild-moderate active ulcerative colitis in 2019.…”
Section: Gut Microbiota/fecal Microbiota Transplantation (Fmt)mentioning
confidence: 99%